1992
DOI: 10.1007/bf00018461
|View full text |Cite
|
Sign up to set email alerts
|

Specific transcription and reinitiation of 2,4-D-induced genes in tobacco nuclei

Abstract: In order to study the effects of trans-acting factors on cis-acting elements in plant genes an in vitro reinitiating nuclear transcription system is needed. Here we report that run-on experiments with nuclei isolated from 2,4-D-treated auxin-starved early-stationary-phase cells of tobacco clearly show reitintiation of transcription of specific 2,4-D-induced genes. Using gamma-thio nucleotides and [alpha-32P]-UTP we were able to demonstrate the presence of reinitiated labelled specific RNAs after isolation on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
(26 reference statements)
2
1
0
Order By: Relevance
“…Higher total RNA accumulation in C. vulgaris cells in response to IM is also consistent with observations that auxin application to whole plants, excised organs or cell cultures leads to a rapid increase in levels of numerous mRNAs (Raghavan et al 2006). In vitro transcription studies with isolated nuclei showed that accumulation of those mRNA species was due to enhanced transcription rates and 2,4-D-dependent stimulation of RNA polymerase II activity (Mennes et al 1992). …”
Section: Discussionsupporting
confidence: 65%
“…Higher total RNA accumulation in C. vulgaris cells in response to IM is also consistent with observations that auxin application to whole plants, excised organs or cell cultures leads to a rapid increase in levels of numerous mRNAs (Raghavan et al 2006). In vitro transcription studies with isolated nuclei showed that accumulation of those mRNA species was due to enhanced transcription rates and 2,4-D-dependent stimulation of RNA polymerase II activity (Mennes et al 1992). …”
Section: Discussionsupporting
confidence: 65%
“…The elution profile of 3H-UMP-labelled in vitro transcripts from the mercury Sepharose affinity column was very similar to what has been reported for animal [3], yeast [4] and other plant [8] nuclei (Fig. 1A).…”
supporting
confidence: 62%
“…To circumvent this problem, the successful use of fl-thio nucleoside triphosphates has been reported [ 12]. Although affinity labelling of RNA has also been described in plant nuclei [5,8], the possibility of post-transcriptional transfer of the 7-thiol group has not been examined in detail. From the data presented here it is clear that inhibition of signals by heparin does not prove reinitiation.…”
mentioning
confidence: 99%